Egg Functionality and Quality During Long-Term Storage - Jones, D.R. (International Journal of Poultry Science, 2007)
Eggs are truly a functional food and the ability of the egg to contribute to food systems is important. The current study was undertaken to determine the changes in functional characteristics and quality factors of commercial shell eggs during 10 wk of 4 °C storage. Commercially processed eggs were collected for three consecutive weeks (reps) from an in-line facility. Analyses were conducted the day after collection (0 wk) and each subsequent week. Total solids for the albumen, yolk and whole egg were determined. Functional properties were examined via preparation of angel food cakes, mayonnaise and sponge cakes. Color was also measured for both raw yolks and prepared mayonnaise. Albumen solids were fairly consistent during storage (12.2 to 12.6%). Whole egg solids remained constant. Yolk solids decreased throughout storage (48.2 to 43.2%). Angel food cake volume decreased as the egg aged. Sponge cake volumes were inconsistent throughout testing with no clearly apparent trends. Mayonnaise was tested immediately after preparation (fresh) and incubation at 50°C for 7 d. In both cases, the average force required to compress the mayonnaise decreased with egg age. Differences were detected for changes in color values (L*, a* and b*) for yolks over time, but these changes were not generally of a magnitude great enough to be seen by the human eye. Most of the measured parameters exhibited significant interactions for replicate and egg storage. These interactions show that variability exists within the testing methods and more objective methods for determining shell egg functionality need to be developed.